Atividade vasorrelaxante do 2-nitro-1-fenil-1-propanol em preparações vasculares isoladas de ratos - Brito, Teresinha Silva de (2015)
2-Nitro-1-phenyl-1-propanol (NPP) is a nitro-alcohol used as a chemical intermediate in the synthesis of ephedrine and norephedrine, sympathomimetic agonists. Its chemical structure resembles the norephedrine, with replacement of the NH2 group by NO2. The presence of the nitro group led us to consider that this compound is able of produce vasodilatory effect, since it was demonstrated in a previous study the vasodilator actions of the nitro compound 1-nitro-2-phenylethane, resulting from stimulation of the guanylate cyclase-cGMP pathway. Our aim was to characterize the effect of on rat isolated vessels. Isometric contractions of isolated rings of thoracic aorta or 2nd-3rd generation branchs mesenteric artery of Wistar rats were recorded by data acquisition system. Cyclic nucleotide levels were measured by ELISA. Signals of strength and calcium fluorescence were simultaneously captured in confocal microscope connected to the data acquisition system. On isolated aorta with intact endothelium, NPP relaxed preparations contracted with phenylephrine (1 µM), K+ (60 mM) or U-46619 (0.3 µM) with EC50 of 30.2 [25.5 - 35.7], 31.8 [27.1 - 37.3] and 28.5 [23.1 - 35.2] µM, respectively. Conversely, in mesenteric vessels, NPP relaxed preparations contracted with phenylephrine (10 µM), K+ (60 mM) or U-46619 (1 µM) with EC50 of 0.41 [0.31 - 0.55], 0.16 [0.10 - 0.24] and 15.1 [10.4 - 24.4] µM, respectively, showing higher potency of NPP in these tissues. The extracellular K+ concentration increase produced gradual decrease in the relaxant effect of the NPP in mesenteric vessels. Pre-treatment with TEA had no effect in the relaxant effect of NPP in aortic rings, however, pretreated mesenteric vessels with TEA, BaCl2, CsCl ou apamin responded less to NPP. Pre-treatment with indomethacin, glybenclamide, 4-aminopyridine or L-NAME did not affect the vasorelaxant effect of the NPP in either aorta or mesenteric vessels. However, its potency was significantly reduced by ODQ (guanylate cyclase inhibitor), MDL-12,330A (adenylate cyclase inhibitor), H-89 (PKA inhibitor) or bisindolylmaleimide IV (PKC inhibitor) pre-treatment. NPP inhibited the vasoconstriction induced by Ca2+ in aorta pre-contracted with phenylephrine or K+, an effect prevented by pretreatment with ODQ or MDL-12,330A. Furthermore, NPP showed a tendency to increase the levels of cAMP and cGMP in aortic rings. The vasorelaxant activity of the NPP was higher in the presence of Y-27632, a Rho- kinase inhibitor. In mesenteric vessels, NPP inhibited both the strength and the calcium fluorescence intensity, indicating that this compound is able to decrease the cytosolic concentration of this ion. So, NPP has vasodilatory action with higher potency in mesenteric vessels. The mechanisms involved in it effect appear to involve the participation of cyclic nucleotides, the control of Ca2+ influx and the regulation of sensitivity of contractile filaments to Ca2+. Moreover, evidences support that the opening of potassium channels is involved in it effect in mesenteric vessels, but not in aortic.